2020
DOI: 10.1007/s00259-020-05055-8
|View full text |Cite
|
Sign up to set email alerts
|

Improved cancer detection in Waldeyer’s tonsillar ring by 68Ga-FAPI PET/CT imaging

Abstract: Purpose In cancer of unknown primary (CUP), positron emission tomography/computed tomography (PET/CT) with the glucose analog [18F]FDG represents the standard imaging approach for localization of the malignant primary. Frequently, however, [18F]FDG PET/CT cannot precisely distinguish between small occult tumors and chronic inflammation, especially in Waldeyer’s tonsillar ring. To improve the accuracy for detecting primary tumors in the Waldeyer’s tonsillar ring, the novel PET tracer [68Ga]Ga-FAPI-4 for specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
119
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(129 citation statements)
references
References 32 publications
(40 reference statements)
7
119
3
Order By: Relevance
“…68 Ga-FAPI-04 also demonstrated a clearer tumor delineation, and a higher tumor-to-background contrast (3). However, in a study with lymph node metastasis of head and neck tumor, Serfling et al observed that 68 Ga-FAPI-04 was not as sensitive as 18 F-FDG (47% vs. 82%) (27). Qin et al also reported that 68 Ga-FAPI-04 outperforms 18 F-FDG in delineating the primary tumor and detecting suspected distant metastases, but cannot detected as many positive lymph nodes as 18 F-FDG (48 vs 100) (23).…”
Section: Introductionmentioning
confidence: 99%
“…68 Ga-FAPI-04 also demonstrated a clearer tumor delineation, and a higher tumor-to-background contrast (3). However, in a study with lymph node metastasis of head and neck tumor, Serfling et al observed that 68 Ga-FAPI-04 was not as sensitive as 18 F-FDG (47% vs. 82%) (27). Qin et al also reported that 68 Ga-FAPI-04 outperforms 18 F-FDG in delineating the primary tumor and detecting suspected distant metastases, but cannot detected as many positive lymph nodes as 18 F-FDG (48 vs 100) (23).…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, CAF-S4 promotes matrix remodelling and cancer cell invasion [59]. Moreover, Ser ing et al [33] suggested a correlation between FAPα lymph node metastases expression and lesion size (weak FAPα expression in lesion < 7 mm, which resulted negative at imaging). Therefore, we can infer that the relatively low performance of [ 68 Ga]Ga-FAPI in detecting nodal metastases reported in some studies may be related to cancer biology and the cell enrichment within lymph nodes.…”
Section: Discussionmentioning
confidence: 99%
“…One study was designed as a phase I investigation [24]. In 12/23 studies [ 68 Ga]Ga-FAPI was offered as a compassionate drug according to the German Medicinal Product Act § 13(2b) [25,26,35,36,[27][28][29][30][31][32][33][34]. In the remaining 10/23 papers, the trial phase was not speci ed or designated as "not applicable" [37][38][39][40][41][42][43][44][45][46].…”
Section: Systematic Reviewmentioning
confidence: 99%
“…Immunohistochemistry (IHC) for FAP (antibody ab207178, Abcam, 1:250) was performed on formalinfixed paraffin-embedded tissue slides according to standard IHC protocols. Immunostaining was scored as previously described [39,40]. In brief, semi-quantitative analysis of stromal staining was scored as 0 (no staining), 1 + (1-10%), 2 + (11-50%), and 3 + (51-100% stromal staining).…”
Section: Histopathological Analysismentioning
confidence: 99%